Identification the coaches' opinions on technical and tactical training of a handball goalkeeper - Chirut, A.; Ghervan, P. (The annals of the "Stefan Cel mare" University, 2019)
The purpose of this research was to identify the coaches' opinions regarding the specific training of the goalkeepers. This aspect will help us to develop a training model that will improve the technical and tactical elements of the players. In this research we started from the hypothesis that the opinion of the investigated specialists will guide us in the elaboration of the technical and tactical training program. Also, we believe that the questions addressed to the specialists will be starting points in the scientific argument of the preparation of the players on the goalkeeper position. The study was based on the survey method. The questionnaire was applied to 42 specialists, with great results in handball. The subjects are handball coaches of the junior and senior teams in Romania. The results showed that the technical and tactical training requires special attention in the training of the goalkeepers because its level conditions the obtaining of superior results of the team in the competition.